2022
DOI: 10.1073/pnas.2200363119
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic intracellular exchange of nanomaterials’ protein corona perturbs proteostasis and remodels cell metabolism

Abstract: Significance This study analyzed the dynamic protein corona on the surface of nanoparticles as they traversed from blood to cell lysosomes and escaped from lysosomes to cytoplasm in the target cells. We found with proteomic analysis an abundance of chaperone and glycolysis coronal proteins (i.e., heat shock cognate protein 70, heat shock protein 90, and pyruvate kinase M2 [PKM2]) after escape of the nanoparticles from lysosomes to the cytosol. Alterations of the coronal proteins (e.g., PKM2 and chape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 59 publications
1
55
0
Order By: Relevance
“…The composition of the corona confers biological identity to NMs and probably directs further interactions with proteins, cells, tissues, etc. 3 , 4 . The formation and evolution of protein corona are thermodynamic and kinetics processes, during which dynamic exchange of corona components is based on different abundance and diffusion rates of proteins, and varying affinities of different proteins binding to the NMs.…”
Section: Introductionmentioning
confidence: 99%
“…The composition of the corona confers biological identity to NMs and probably directs further interactions with proteins, cells, tissues, etc. 3 , 4 . The formation and evolution of protein corona are thermodynamic and kinetics processes, during which dynamic exchange of corona components is based on different abundance and diffusion rates of proteins, and varying affinities of different proteins binding to the NMs.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of protein crowns will reshape the metabolic behavior of nanocarriers in vivo, causing non-specific phagocytosis while triggering a series of side effects including autoimmune response, apoptosis or necrosis and inflammation. In recent years, Chen et al 47 identified the protein corona effect also restricted the delivery efficiency of nanomedicine and affected drug release in animals, which might also contribute to the poor therapeutic effect.…”
Section: Discussionmentioning
confidence: 99%
“…In an environmental context, pristine nanomaterials transform and obtain a corona of biomolecules, such as proteins, which shields the identity of a nanoparticle, possibly affecting the long circulation and targeting efficiency. 39 Although the orientation and conformation of bound proteins are thought to be strong indicators of cellular uptake, the nature of proteins, characterization of corona composition, and geometry of the nanomaterial will also play key roles in nano−bio interactions.…”
Section: Protein Corona: Passive Adsorption and Endogeneous Regulationmentioning
confidence: 99%